Prophetic Practice and Legal Significance: Al-Ghazālī’s Critique of Textualism in al-Mankhūl - Abdurrahman, Landy Trisna; Anshori, Ahmad Yani (UIN Sunan Kalijaga, 2023)
The methodological framework proposed by al-Ghazali in al-Mankhūl min Ta’līqātil Uṣūl offers a balanced perspective on the Prophet’s conduct by classifying his actions according to the objectives of the Sharia (maqāṣid ash-Sharia), contextual indicators (qarīnah), and their relation to local custom (‘urf). This classification enables a clear distinction between actions that are normatively binding and those that reflect the socio-cultural practices of the 7th-century Prophetic era. Such an approach avoids the extremes of literalism, which absolutizes all Prophetic behavior as obligatory, and relativism, which dismisses the normative dimension of the Sharia by reducing the Prophet’s conduct to mere socio-cultural products. The analysis is reinforced by an in-depth discussion of the roles of ‘urf and maṣlaḥah as instruments that bridge the textual tradition with social realities. ‘Urf helps identify local and temporal elements within the Prophet’s actions, while maṣlaḥah ensures that legal adaptations remain oriented toward recognized benefits under the Sharia. This study adopts a qualitative, library-based research method, examining al-Mankhūl both textually and contextually, and reassessing the connection between al-Ghazali’s methodological framework and the practice of legal derivation (istinbāṭ al-ḥukm). The critique of textualism and hadith-centrism underscores the urgency of this approach, as both tendencies risk neglecting social context and the aims of public welfare. The findings show that al-Ghazali’s methodology integrates theological, legal-theoretical, and jurisprudential dimensions into a unified epistemic structure, paving the way for an Islamic legal methodology that is more responsive to contemporary social dynamics while maintaining normative legitimacy, and is relevant for the development of fatwas and religious policy.Kerangka metodologis yang ditawarkan al-Ghazali dalam al-Mankhūl min Ta’līqātil Uṣūl memberikan cara pandang yang proporsional terhadap perilaku Nabi dengan mengklasifikasikan tindakan-tindakannya berdasarkan tujuan-tujuan syariat, qarīnah (keterikatan) konteks, serta keterkaitannya dengan ‘urf (lokalitas). Melalui klasifikasi ini, dimungkinkan pemisahan antara tindakan yang bersifat normatif mengikat dan tindakan yang merefleksikan kebiasaan sosial-budaya pada masa Kenabian (Abad 7 Masehi), sehingga terhindar dari jebakan literalisme yang memutlakkan seluruh perilaku Nabi menjadi wajib diikuti, atau bahkan relativisme yang menanggalkan dimensi normatif syariat – karena anggapan perilaku Nabi adalah sebatas produk sosial-budaya. Analisis ini diperkuat dengan pembahasan mendalam mengenai peran ‘urf dan maṣlaḥah sebagai instrumen yang menjembatani teks dengan realitas sosial. ‘Urf membantu mengenali unsur-unsur lokal dan temporal dalam perilaku Nabi, sedangkan maṣlaḥah memastikan bahwa adaptasi hukum tetap berorientasi pada kemaslahatan yang diakomodir oleh syariat. Penelitian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan, dengan menelaah al-Mankhūl secara tekstual dan kontekstual, serta meninjau ulang keterkaitan antara kerangka metodologis al-Ghazali dengan praktik istinbat hukum. Kritik terhadap tekstualisme dan hadisisme menegaskan urgensi pendekatan ini, mengingat keduanya berpotensi mengabaikan konteks sosial dan tujuan kemaslahatan. Temuan dalam artikel ini menunjukkan bahwa metodologi al-Ghazali merekatkan dimensi teologis, usul fikih, dan fiqih dalam satu kesatuan epistemik, membuka ruang bagi metodologi hukum Islam yang lebih adaptif terhadap dinamika sosial kontemporer tanpa kehilangan legitimasi normatifnya, serta relevan bagi pengembangan fatwa dan kebijakan keagamaan.